Klippel-Trenaunay-Weber syndrome with hydronephrosis and vesicoureteral reflux: an unusual association - Yıldızdaş, Dinçer; Antmen, Bülent; Bayram, İbrahim; Yapıcıoğlu, Hacer (The Turkish Journal of Pediatrics, 2002)
The Klippel-Trenaunay-Weber syndrome is a rare disorder characterized by congenital vascular hamartomas, limb hypertrophy, cutaneous manifestations, lymphangiomas and atresia of lymph vessels with non-pitting edema. A three-year-old boy was referred to our clinic for progressive hypertrophy of leg and feet with 32-month history. We diagnosed Klippel-Trenaunay-Weber syndrome, and determined vesicoureteral reflux in our patient. To our knowledge, hydronephrosis and vesicoureteral reflux have not been described previously in the KTWS.
Keywords: Klippel-Trenaunay-Weber syndrome; hydronephrosis; vesicoureteral reflux